Determinants of Market Power in Electric Power Market of Rural Areas in Nigeria: Array - Ojo, Ademola Eyitope (Acta Universitatis Danubius. Œconomica, 2020)
Electricity is central to socioeconomic growth and development of any economy. And, the electrical power sector of many economies has witnessed reforms in recent time, transforming into competitive and or oligopolistic market structure. In any case, energy pricing subsist as a challenge across the power value chain. This study focused identifying the determinants of market power of energy distributing operation and rural area consumers in the power retail market in Nigeria’s present oligopolistic power market structure. Adopting a production function model and econometric analysis of selected power sector time series variables between 2000-2017, the study discovered that electrical power generation, rural electricity access and energy consumption in Nigeria are though essential but do not ultimately and significantly determine market power of competing firms in the electric power market in Nigeria. It is concluded that evidence of the importance of market power for competing firms in the electric power conduct in terms of energy pricing and cost decisions is auspicious considering their prevailing market challenges. The study therefore recommend amongst others for exclusive regional or sub regional power chain structural transformation of Nigerian electrical power in order to help build efficient and effective energy supply thereby elicit information/data for control, improvement, competition and researches in the sector while Future research on market power in electrical power market is encourage on assumptions.